2023
DOI: 10.3390/agronomy13040979
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Application of Multi-Walled Carbon Nanotubes (MWCNTs) and Nano-Selenium (Nano-Se) Alleviated the PEG-Induced Water Deficit Stress and Improved the Crop Performance of Camelina

Abstract: While previous studies have shown camelina drought tolerance relative to other oilseed crops, drought has been documented to severely influence the productivity of camelina. To date, little information is available on the drought tolerance of camelina genotypes. This study was conducted to evaluate drought tolerance in fifteen camelina genotypes and test the alleviative effect of nanoparticles on PEG-induced water deficit stress (WDS) at the whole-plant level at the Yangzhou University Pratacultural Science Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…[25] and wheat (Triticum aestivum L.) [24], showed that the exogenous application of nano-Se could potentially increase the contents of defense-related chemicals (i.e., flavonoid) in plants and thus enhance plant resilience under unfavorable conditions. Our recent study also showed the potential for using nano-Se to alleviate PEG-induced drought stress and maintain the seed yield and quality in camelina [21].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…[25] and wheat (Triticum aestivum L.) [24], showed that the exogenous application of nano-Se could potentially increase the contents of defense-related chemicals (i.e., flavonoid) in plants and thus enhance plant resilience under unfavorable conditions. Our recent study also showed the potential for using nano-Se to alleviate PEG-induced drought stress and maintain the seed yield and quality in camelina [21].…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to the previous studies reporting an increase in SOD activity in Al 3+ -stressed oilseed rape after melatonin treatment [29] and drought-stressed tomato (Solanum lycopersicum L.) after Se treatment [49], in this study, the SOD and CAT activities of the camelina plants co-applied with melatonin or nano-Se were maintained at a normal level similar to untreated controls. Recently, our research team also observed a relatively stable SOD activity in drought-stressed camelina plants after nano-Se treatment [21]. Because the mechanism differences in melatonin-mediated Al 3+ tolerance vary across different plant species [3] and the various defense mechanisms of plants possessed under various stresses (e.g., alteration of antioxidant enzyme activity, production of defensive pigments) [50], the increase in antioxidant enzyme activities after stress-alleviating chemical treatment may simplify the changing process of these enzyme activities under various stresses.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations